Rookie Reader : The Frog in the Pond - Mara, Wil; Mendenhall, Cheryl (New York : Children's Press, 2007)
When a boy finds a frog down by the pond, he catches it and puts it in a cage, but the frog does not enjoy captivity, in this story told using opposites.
Keywords: English language -- Synonyms and antonyms; Opposites; Early readers